2015
DOI: 10.1371/journal.pone.0133734
|View full text |Cite|
|
Sign up to set email alerts
|

How Diverse Detrital Environments Influence Nutrient Stoichiometry between Males and Females of the Co-Occurring Container Mosquitoes Aedes albopictus, Ae. aegypti, and Culex quinquefasciatus

Abstract: Allocation patterns of carbon and nitrogen in animals are influenced by food quality and quantity, as well as by inherent metabolic and physiological constraints within organisms. Whole body stoichiometry also may vary between the sexes who differ in development rates and reproductive allocation patterns. In aquatic containers, such as tree holes and tires, detrital inputs, which vary in amounts of carbon and nitrogen, form the basis of the mosquito-dominated food web. Differences in development times and mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 67 publications
1
38
1
Order By: Relevance
“…albopictus containers is documented (Murrell et al 2011); however, these data have not been linked to the nutrient composition of adults, nor have any studies linked variation in stoichiometry to components of adult success (e.g., longevity) or the ability to transmit disease (e.g., vector competence). As elements are the basis for both structural components (e.g., chitin) and biological processes (e.g., metabolism), these seem (Yee et al 2015b) under all detritus ratios tested. This suggests that although Ae.…”
Section: Nutrient Stoichiometry and Stable Isotopesmentioning
confidence: 90%
See 3 more Smart Citations
“…albopictus containers is documented (Murrell et al 2011); however, these data have not been linked to the nutrient composition of adults, nor have any studies linked variation in stoichiometry to components of adult success (e.g., longevity) or the ability to transmit disease (e.g., vector competence). As elements are the basis for both structural components (e.g., chitin) and biological processes (e.g., metabolism), these seem (Yee et al 2015b) under all detritus ratios tested. This suggests that although Ae.…”
Section: Nutrient Stoichiometry and Stable Isotopesmentioning
confidence: 90%
“…The data generally support higher overall performance for Ae. albopictus in animal-versus plant-derived diets (Daugherty et al 2000, Yee et al 2007a, Murrell and Juliano 2008, Winters and Yee 2012, Bara et al 2014, Yee et al 2015b); however, Barrera (1996) found that Ae. albopictus survived longer when grown on leaves versus an artificial diet of bovine liver powder and yeast.…”
Section: Nutrient Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrition is an early developmental factor known to modulate life history traits. It is an important factor regarding host-pathogen interactions; as host nutrition influences multiple measures of adult performance, immune response, and the resources necessary for pathogen replication (Lee et al 2006, 2008; Telang et al 2012, Yee et al 2015). Larval nutritional stress can reduce the immune response of mosquitoes allowing for increased pathogen infection (Sindbis virus; Muturi et al 2011) or reduce resources for pathogen development (malaria; Vantaux et al 2016ab).…”
Section: Introductionmentioning
confidence: 99%